Aplicación móvil de monitorización y control de un invernadero doméstico automatizado usando arduino - Cruz Vásquez, Eveling Giselle (2018)
The greenhouses of culture are used to increase the quality and the yield of the crop in the plantations during his time or out of it._x000D_ In this project a model of a greenhouse is made, using the Arduino board and the creation of an application with the Android programming language, in order to control and monitor the control parameters._x000D_ On the one hand, the Arduino board is used as the controller card of the system, and as a data acquirer; In addition, an Android application capable of monitoring and controlling the state of the greenhouse is developed._x000D_ In order to obtain the Arduino and Android connection, web hosting is used, from which a domain is obtained where a database is stored, and saves the data sent by Arduino or Android, as well as being able to manipulate the greenhouse remotely